High expression and biosilica encapsulation of alkaline-active carbonic anhydrase for CO2 sequestration system development. (January 2016) - Min, Ki-Ha; Son, Ryeo Gang; Ki, Mi-Ran; Choi, Yoo Seong; Pack, Seung Pil
Highlights: High pH stable HCA(SP-) was successfully produced in soluble form. HCA(SP-) can retain ∼90% activity even after 2 h-incubation at pH 10. HCA(SP-)@silica can retain over 80% CO2 hydration activity after 10-time reuse at pH 10. Abstract: Carbonic anhydrase (CA) is a biocatalyst for CO2 sequestration because of its distinctive ability to accelerate CO2 hydration. High production and efficient immobilization of alkaline-active CAs are required, because one potential application of CA is its use in the alkaline solvent-based CO2 absorption/desorption process. Here, we designed and applied an α-type CA from Hahella chejuensis (HCA), which was reported as highly active in alkaline conditions, but was mostly expressed as insoluble forms. We found that the signal peptide-removed form of HCA [HCA(SP-)] was successfully expressed in the soluble form [∼70 mg of purified HCA(SP-) per L of culture]. HCA(SP-) also displayed high pH stability in alkaline conditions, with maximal activity at pH 10; at this pH, ∼90% activity was maintained for 2 h. Then, we prepared HCA(SP-)-encapsulated silica particles [HCA(SP-)@silica] via a spermine-mediated bio-inspired silicification method. HCA(SP-)@silica exhibited high-loading and highly stable CA activity. In addition, HCA(SP-)@silica retained more than 90% of the CA activity even after 10 cycles of use in mild conditions, and ∼80% in pH 10 conditions. These results will be useful for the development of practical CO2 sequestration processes employing CA.